ANALISA LAPORAN ARUS KAS UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT. TOPJAYA SARANA UTAMA JAKARTA - Bambang Hermanto; Hamizar Hamizar; Puspita Romadhona (POLITEKNIK LP3I JAKARTA, 2019)
Financial performance is a parameter tool of management success level in managing financial so urces owned by the company. The using statement of cash flow approach in this research is based on that this approach is very good to measure the company performance (management) because it is able to measure the company efficiency in particular periode. Statement of cash flow is the report that showing the effect of operating activities, investing activities, and financial activities in company to cash flow for certain periode by use of method that already being established which is direct method or indirect method. Useful statement of cash flow internally divides management party and externally divides investor party and creditor. With arrange cash flow information analysis, side management will know if policy already is being done by walking with every consideration. Analisis of the statement of cash flow is very important for management as the decision maker. This research objective is to measure the financial performance of PT.Topajaya Sarana Utama. In the periode accounting 2008–2012 through using analysis statement of cash flow with the ratio of investment and financing, adequacy ratio, efficiency ratio. From the research result already been done the writer get a conclude : that PT. Topjaya Sarana Utama get a liquid situation a shows that company able have a capability to pay the short term and long term liabilities in the next futures therefore analysis cash flow can be a tool to evaluate performance of PT. Topjaya Sarana Utama, that besed on companycapability in get the positive cash and result of analysis cash flow to able to realize financial performance effectively and efficiently.Key words: Analysis ,Cash Flow, Financial Performance